Made in China : secrets of China's dynamic entrepreneurs - Nie, Winter; Xin, Katherine; Zhang, Lily. (Singapore ; Hoboken, NJ : Wiley, 2009)
"Insight and analysis on the strategies that have led to China's rapid economic expansion" "China's rapid economic growth has made it a vital market for the biggest multinational corporations, most of which have invested heavily in China. Yet those corporations face their toughest competition not from other multinationals, but from China's own homegrown businesses. China's entrepreneur class has grown and their businesses are succeeding primarily due to their knowledge of the domestic market, quick adaptation to market changes, and their resourcefulness. To paraphrase Sun Tzu, it is best to know one's enemy. Made in China gives executives at multinationals the inside insight they need to compete with China's homegrown businesses before they lose out."--Jacket
Wahaha : Danone's dream partner and nightmare -- Nice : P & G's fierce local competitor -- Taobao : the eBay killer -- Who are they? -- The development of Chinese commerce -- Three stories -- Who are the typical entrepreneurs? -- Business model -- Individual characteristics for their success -- Compete with them -- Collaborate with them.
Includes bibliographical references (pages 205-206) and index.
Print version record.
John Wiley and Sons
Keywords: Entrepreneurship -- China; Business enterprises -- China; Competition -- China; Entrepreneuriat -- Chine; Entreprises -- Chine; Business enterprises; Competition; Entrepreneurship; China; Ondernemerschap; China; Privatwirtschaft; Unternehmer; Internationaler Wettbewerb; 2; Multinationales Unternehmen; 2; China